2006
DOI: 10.1002/chem.200600738
|View full text |Cite
|
Sign up to set email alerts
|

The Mg‐Oppenauer Oxidation as a Mild Method for the Synthesis of Aryl and Metallocenyl Ketones

Abstract: Magnesium alkoxides undergo a hydride‐transfer oxidation with benzaldehyde as the oxidant. This magnesium variant of the Oppenauer oxidation was used for the synthesis of polyfunctional biaryl ketones. LiCl was found to promote this reaction by enhancing the solubility of magnesium alkoxides. This mild oxidation method was especially useful for preparing ketones bearing a metallocenyl unit as well as various new ferrocenyl ketones and tricarbonylchromium complexes. This last class of ketones was reduced with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 117 publications
1
22
0
1
Order By: Relevance
“…19 Interestingly, the presence of LiCl in the reaction mixture considerably accelerated the oxidation reaction. It was suggested that the role of LiCl was both to solubilise the primarily formed magnesium chloride alkoxide and to activate the carbonyl function of benzaldehyde as a Lewis acid.…”
Section: Methodsmentioning
confidence: 99%
“…19 Interestingly, the presence of LiCl in the reaction mixture considerably accelerated the oxidation reaction. It was suggested that the role of LiCl was both to solubilise the primarily formed magnesium chloride alkoxide and to activate the carbonyl function of benzaldehyde as a Lewis acid.…”
Section: Methodsmentioning
confidence: 99%
“…The combined organic layers were washed successively with aqueous 5 % NaHCO 3 and brine, dried (MgSO 4 ), and concentrated in vacuo. Flash chromatography (silica gel; 1 % ethyl acetate in toluene) of the residue gave 0.186 g (94 % yield) of 5a 12 (92 % ee ): HPLC analysis: Chiralcel OD column, 0.5 mL/min, 5 % i PrOH in hexane; retention times: 30.9 min [major ( S ) enantiomer], 34.6 min [minor ( R ) enantiomer]. This data is in agreement with published values 12…”
Section: Methodsmentioning
confidence: 99%
“…Typical MPV-active catalysts are based on transition metal complexes, including aluminum [4,5], boron [6], magnesium [7] and zirconium [8] complexes. Despite the several advantages of these homogeneous catalysts, their heterogeneous counterparts are preferred because of practicality, due to their easier separation from the reaction media or their higher resistance against moisture.…”
Section: Introductionmentioning
confidence: 99%